Practices for Improving Secondary School Climate: A Systematic Review of the Research Literature. Issue 1 (18th August 2016) - Voight, Adam; Nation, Maury
Abstract: School climate has received increased attention in education policy and, in response, educators are seeking strategies to improve the climates of their middle and high schools. However, there has been no comprehensive synthesis of the empirical evidence for what works in school climate improvement. This article constitutes a systematic review of programs and practices with empirical support for improving school climate. It defines school climate and provides a methodology for identifying and evaluating relevant studies. The review identified 66 studies with varying strength of evidence and nine common elements that cut across reviewed programs and practices. The review concludes with a critical appraisal of what we know about school climate improvement and what we still need to know.